A Case of Symptomatic Intraluminal Internal Carotid Artery Thrombus in a Patient with Essential Thrombocythemia Surgically Treated by CEA - Satoshi Takahashi; Masahiro Katsumata; Hirotsugu Nogawa; Kento Takahara; Jin Nakahara; Masahiro Toda (Case Reports in Neurological Medicine)
We report a patient with a symptomatic intraluminal internal carotid artery thrombus clinically revealed by cerebral infarction. In the preoperative evaluation, it was revealed that essential thrombocythemia existed in the background. Therefore, medical treatment with antithrombotic agents in conjunction with hydroxycarbamide for essential thrombocythemia was initiated, but the thrombus was not dissolved by three weeks. At this time, the patient underwent carotid endarterectomy, which removed the thrombus completely with its adjacent plaque without any perioperative stroke. The possibility of essential thrombocythemia may also be kept in mind when an increased platelet count is observed in patients with internal carotid artery thrombus. It is a reasonable option to precede medical treatment, including anticoagulant therapy, by setting the time limit for surgical intervention in such a disease state.